Hypomagnetic fields cause anxiety in adult male mice. Issue 1 (26th November 2018) - Ding, Hai‐min; Wang, Xue; Mo, Wei‐chuan; Qin, Ling‐ling; Wong, Steven; Fu, Jing‐peng; Tan, Yan; Liu, Ying; He, Rong‐qiao; Hua, Qian
Abstract : Hypomagnetic fields (HMF), that is, the elimination of the geomagnetic field (GMF), are a risk factor to the health of astronauts in outer space. It has been established that continuous HMF exposure affects cytoskeleton assembly, cell proliferation, embryonic development, and even learning and memory. In addition, although there were some previous studies that focused on the effects of long‐term HMF‐exposure, so far very limited investigations have been conducted to examine the short‐term HMF effect in animals. In this study, we exposed adult male C57BL/6 mice to a 3‐axis Helmholtz‐coil HMF‐simulation system for 72 h and found that short‐term HMF‐exposure induced a significant increase in anxiety‐related behaviors. And our findings provide important information for both psychological intervention and the health care of astronauts. Bioelectromagnetics. 40:27–32, 2019. © 2018 Wiley Periodicals, Inc.